Lokalno podnebje in topoklimatska karta Jezerskega - Ogrin, Darko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2016)
The article deals with basic topoclimatic features of Jezersko resulting from the general climate characteristics and specific local conditions. The spatially most widely spread topoclimatic units result from insolation differences and interaction between local landform features and land use. They are presented on a generalized topoclimatic map in the scale of 1 : 25,000.
Keywords: climate; climatology; Jezersko; klimatologija; microclimate; mikroklima; podnebje; relief; Slovenia; Slovenija; topography